Answer:
![a_n=-3+4(n-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/6gosc64j9lr89qiuoo09312vxxxic411mf.png)
Explanation:
This sequence can be interpreted as an arithmetic sequence, which has a general equation in the following format:
![a_n=a_1+d(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/z9jyjzs3gtye2ac99tljhz0dstsxu67bsc.png)
In which a1 is the first term and d is the common ratio(the difference between the consecutive terms.
In this sequence:
The first term is -3.
The common ratio is ... = 9 - 5 = 5 - 1 = ... = 4
So the equation for the sequence is:
![a_n=-3+4(n-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/6gosc64j9lr89qiuoo09312vxxxic411mf.png)